Nova Scotia : a health system profile. - Fierlbeck, Katherine (Provincial and territorial health system profiles., 2018)
"Despite notable variation in health care policy from province to province, most scholarship published on the health care system in Canada uses a broad national perspective. Focusing on the health care systems of individual Canadian provinces and territories, this new series, Health System Profiles, examines the social, political, economic, and epidemiological context of health care policy in each Canadian province. Turning a critical eye to the health care system in Nova Scotia, author Katherine Fierlbeck outlines the organizational and regulatory frameworks structuring provincial health care, while providing a detailed assessment of Nova Scotia's health financing, physical infrastructure, service provision, and the efficacy of technological resources used in data tracking and health quality assessments. Structured for ease of comparison, Nova Scotia: A Health System Profiles will, along with other volumes in the series, help scholars draw analytic evidence-based policy conclusions about the health system of Nova Scotia and other Canadian provinces and territories."--